Food hygiene knowledge, attitudes and practices among food handlers in restaurant in Selayang area - Ghazali, Hazrina (2012)
Food handlers are responsible in providing safe food for the consumption of their customers. Hence, it is compulsory for them to undergo food handler training upon working in any foodservice establishments in order to gain knowledge and understand the importance of food hygiene. In spite of that, foodborne illnesses seem to become more common in Malaysia and there are cases of where foodservice operators receive warning letters from the authority regarding the cleanliness issue. Therefore, this study is aimed to identify the level of knowledge, attitudes and practice of food handlers towards food hygiene. The types of practice that the food handlers applied in restaurant industry are also examined. Moreover, the influence of socio demographic towards food handlers’ knowledge, attitudes and practice are also examined as part of the purpose. In order to achieve these objectives, survey was done through distribution of questionnaires to the employees of medium scale restaurants in Selayang, Selangor area. Convenience sampling was used to select the target. Data analysis was done by using Statistical Packages for Social Science (SPSS) 19.0. Findings shown that the food handlers have knowledge about food hygiene although it is revealed that some food handlers do not have the knowledge towards washing hand procedure and the temperature danger zone. Furthermore, even though they are found to have moderate attitudes towards food hygiene, the food handlers have positive attitudes towards several practices. In terms of socio demographics, the results proved that marital status, age, awareness, and training influenced the food handlers’ attitudes towards food hygiene. Moreover, awareness and training influenced the food handlers practice. In conclusion, food handlers of restaurants in Selayang have awareness towards food hygiene knowledge, attitudes and practice. However, there are needs to increase their level of awareness.